Tratamento de efluentes contaminados com paracetamol através da adsorção em batelada e coluna de leito fixo - Penha, Vitória Cibely Silveira (Universidade Federal Rural do Semi-Árido, 2020)
Currently there is great concern about the contamination of water and the search for new effluents treatment methods because research showed the presence of emerging micropollutants in surface water and groundwater. Among these micropollutants, there are drugs, and because it is widely used worldwide, paracetamol is one of the most commonly found in wastewater. The existing methods in Water Treatment Plants (WTPs) are not effective in removing these substances from the water, which implies having a cumulative effect on the water. In view of the need to find an adequate treatment for the removal of these pollutants, the present work seeks to bring a viable alternative for the treatment of effluents contaminated with paracetamol through adsorption using a commercial activated carbon as an adsorbent. For this, a study of a continuous process (fixed bed) and a discontinuous process (batch) was carried out, in which the effect of the solution pH, the reaction equilibrium time and the adsorbed amount of paracetamol for this carbon were analyzed. The carbon was characterized in relation to the zero charge point and in relation to its textural properties, by means of nitrogen adsorption isotherms (N2) at 77 K. In the evaluation of the activated carbon as an adsorbent, tests of kinetics and isotherms of adsorption, and the fixed bed test. After all the study and analysis of the results it is possible to state that the activated carbon Norit GAC 1240 is promising in the removal of paracetamol in aqueous solution, presenting equilibrium time around 12 h and the amount adsorbed in the equilibrium concentration of ca. 167 mg/g that it is superior when compared to literature data, moreover, in the fixed bed test it has been shown to have a great adsorption capacity.
Keywords: Adsorção; carbono ativado; micropoluentes; paracetamol; fármacos; ENGENHARIAS::ENGENHARIA QUIMICA